Pengaruh Kompensasi, Motivasi, Dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. Saiba Cipta Selaras Kota Jakarta Selatan - Aditya Trisna; Eddy Guridno (Fakultas Ekonomi dan Bisnis Universitas Nasional, 2021)
PurposeThis study aims to determine and analyze the effect of compensation, motivation and work environment on employee performance. Methodology This research data uses primary data in the form of a questionnaire to 100 employees of PT. Saiba Cipta Selaras. Data analysis technique using multiple linear regression analysis and using SPSS program. Findings The results showed that there was an influence between compensation, work motivation and work environment on employee performance. Partially or simultaneously had a strong influence among the three variables, the most significant of which was the work environment variable. Suggestions The results of this study hope that the company can improve a safe and comfortable working environment because this is the most significant factor affecting the performance of PT. Saiba Cipta Selaras employees.